VULNERABILE ESTIMATION OF THE LANDMASS EROSION AND THE SEDIMENT YIELD IN THE INNER PART OF MAUAKOS GULF DRAINAGE BASIN - ΣΙΓΑΛΟΣ ΓΕΩΡΓΙΟΣ; ΑΛΕΞΟΥΛΗ-ΛΕΙΒΑΔΙΤΗ ΑΛΙΚΗ (Bulletin of the Geological Society of Greece, 2005)
The geomorphology and the lithology of an area is the basic factor that controls the erosional. Capability of the exogenic processes principally by the action of the water. In order to investigate the intensity and the erosion that can be seen in every area we followed the following methodology. We prepared a series of maps at scale 1:50.000. These maps helped us to work out and analyze the factors that affected the configuration of the relief. These maps are relative to the lithology of the formations, as well as their behavior under the affect of the exogenic processes in connection with he morphological slope. The maps that we prepared can be divided into three groups: A map providing information about the lithology and hydrogeology. In this map, two areas are distinguished according to the behavior and resistivity to erosion. Maps providing geomorphological data due to the shape and the evolution of the drainage networks of the area. In order to investigate the drainage texture, drainage density and drainage frequency maps were prepared. In each of these maps, three different areas of density and frequency values were distinguished. A combination of these maps leads to a final map of the drainage texture in which two different areas can be distinguished. A map of the slope of the valley sides. According to the gradient values of the slopes, two areas were distinguished. One area with gradient of less than 12% and one of more than 12%. The value of 12% was considered as a marginal value. The combination of the three final maps, of drainage texture, relief slopes and lithologie areas susceptible to erosion produced the erosivity map. According to erosivity three different categories of areas were distinguished. As the map shows the larger part of the area belongs to the category of low erosivity. Finally due to investigate the erosivity under present conditions we combined the erosivity map with the vegetation cover map. It is appreciated that the erosivity of the formations whish are covered of forests is significantly protected from erosivity and decreased than those of uncultivated areas